The human computer interaction in the curricula of Colombian higher educative institutions - Riascos-Pareja, Carlos Andrés; Loaiza-Duque, Álvaro Andrés; Estrada-Esponda, Royer David (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The article addresses the current state of the inclusion of subjects related to the Human Computer Interaction, HCI, in the curricula of Higher Education Institutions, HEI, of Colombia. The research methodology had an exploratory and descriptive scope, besides having a quantitative cut. The research contemplated the 497 active HEI as a target population to April 2017. The results highlight that at least 137 HEI offer core programs of Computers Engineering, Telematics and related topics, which according to the National Information System of Superior Education, SNIES, group the institutions that offer training programs in the computing field. The latter ones, only 28.47% offer 42 subjects related to the HCI. In addition, of all the graduates in 2015 from careers of this group, at least 4.36% of them could have knowledge of the discipline. This allows us to conclude that the skills or competences in the field of the HCI, in the professional profiles of Colombian graduates, are minimal in terms of this topic.